Indonesian tenth graders’ academic self-efficacy and English achievement admitted through zoning and achievement schemes - Hartono, Hartono; Arjanggi, Ruseno; Nugroho, Kurniawan Yudhi (Institute of Advanced Engineering and Science, 2025)
The zone-based new student admission scheme for lower and secondary public schools has significantly changed education practices, not only in the admission policy but also in the teaching and learning practices. This study aims to describe and compare academic self-efficacy and the achievement of Indonesian tenth-graders admitted through the zoning and achievement admission schemes. Five public senior high schools were purposively selected as samples to represent different clusters of school preferences before the zoning scheme was implemented. Data were collected through an academic self-efficacy questionnaire specially prepared for the study and an achievement test conducted by the classroom teachers. A total of 483 tenth graders completed the questionnaire and an English achievement test; among them, 74.3% were admitted through the zoning scheme, 17.6% were through the achievement scheme, and the remaining 8.1%, were through affirmation, transfer of parent’s job, and other schemes. Data were analyzed descriptively and inferentially using SPSS. The tenth graders had a high level of academic self-efficacy. However, there was a significant difference in academic self-efficacy and English achievement between the tenth graders admitted through the zoning scheme and those admitted through the achievement scheme. The causes of the difference and the implications are discussed.